Nitroglycerin Ointment for Reducing the Rate of Mastectomy Flap Necrosis in Immediate Implant-Based Breast Reconstruction. Issue 3 (September 2018) - Turin, Sergey Y.; Li, Daniel D.; Vaca, Elbert E.; Fine, Neil
Abstract : Background: Mastectomy flap necrosis remains a challenging complication in immediate tissue expander breast reconstruction. Nitroglycerin ointment has been shown to reduce the incidence of mastectomy flap necrosis in a randomized controlled study, using 45 g per breast and treating one side only in bilateral cases. This study was conducted to determine the efficacy of 15 g of nitroglycerin ointment per breast, therefore permitting application to both breasts in cases of bilateral mastectomy. Methods: A retrospective cohort study of patients undergoing immediate tissue expander breast reconstruction performed by a single reconstructive surgeon was conducted. The intervention cohort consisted of all patients between June 10, 2015, and June 9, 2016 (94 patients, 158 breasts), where 15 g of nitroglycerin ointment was routinely applied per breast. The control cohort consisted of all patients from June 10, 2014, to June 9, 2015 (107 patients, 170 breasts), where nitroglycerin was not applied. All complications were tracked, including minor wound healing problems. Results: There was an overall 22 percent decreased incidence of mastectomy flap necrosis in the nitroglycerin ointment cohort (47.5 percent versus 60.6 percent; p = 0.002), with a 44 percent reduction in full-thickness mastectomy flap necrosis that trended toward statistical significance (9.5 percent versus 16.5 percent; p = 0.06). On multivariate analysis, nitroglycerin application was independently associated with a decrease in mastectomy flap necrosis or need for mastectomy flap débridement. There was no significant difference in the incidence of postoperative hypotension (3.8 percent versus 2.9 percent) or headache among cohorts. Conclusion: Topical nitroglycerin ointment application to mastectomy skin flaps at 15 g per breast is a cost-effective means of decreasing the incidence of mastectomy flap necrosis in unilateral and bilateral immediate tissue expander breast reconstruction. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III. Abstract : This and Related "Classic" Articles Appear on Prsjournal.com for Journal Club Discussions.